Genomics and resequencing of Fagopyrum dibotrys from different geographic regions reveals species evolution and genetic diversity - Zheng, Si-hao; Diao, Yong-chao; Du, Jie; Li, Jin-tong; Zhao, Sha; Liu, Mei-juan; Lin, Hui-cai; Zeng, Yan; Wang, Ji-yong (Frontiers in Plant Science, 2024)
Fagopyrum dibotrys, belonging to the family Polygonaceae and genus Fagopyrum, is used in traditional Chinese medicine and is rich in beneficial components, such as flavonoids. As its abundant medicinal value has become increasingly recognized, its excessive development poses a considerable challenge to wild germplasm resources, necessitating artificial cultivation and domestication. Considering these factors, a high-quality genome of F. dibotrys was assembled and the evolutionary relationships within Caryophyllales were compared, based on which 58 individual samples of F. dibotrys were re-sequenced. We found that the samples could be categorized into three purebred populations and regions distributed at distinct elevations. Our varieties were cultivated from the parental populations of the subpopulation in central Yunnan. F. dibotrys is speculated to have originated in the high-altitude Tibetan Plateau region, and that its combination with flavonoids can protect plants against ultraviolet radiation; this infers a subpopulation with a high accumulation of flavonoids. This study assembled a high-quality genome and provided a theoretical foundation for the future introduction, domestication, and development of cultivated varieties of F. dibotrys.